Effect of Air Abrasion and Erbium-Doped Yttrium Aluminum Garnet (Er: YAG) laser preparation on Shear Bond Strength of Composite to Dentin - Pahlavan, Ayoub; Mehmanchi, Mobin; Ranjbar Omrani, Ladan; Chiniforush, Nasim (Journal of Lasers in Medical Sciences, 2013)
Introduction: The aim of this study was to assess shear bond strength of composite to dentin after air abrasion and laser treatment. Methods: 40 human extracted molars divided into 4 groups (n=10) received the following treatments. Group 1: carbide bur, Group 2: air abrasion with aluminum oxide 50 μm, Group 3: irradiated with Erbium-Doped Yttrium Aluminum Garnet (Er: YAG) laser (150 mJ/20Hz), Group 4: irradiated with Er:YAG laser (150 mJ/20Hz)+ air. Specimens in all groups were chemically etched with phosphoric acid 37% and treated with bonding agent (single bond 3M). Then, composite build-up was performed by tygon tube. After storage in distilled water at 37°c for one week, all specimens were subjected to a shear bond strength test with universal testing machine. Data were analyzed with ANOVA and T-Test. Results: The mean and standard deviation of shear bond strength of the 4 groups were 20.8±6.76, 14.98±3.98, 11.43±4.36 and 14.95± 3.18 MPa, respectively. Conclusion: Air abrasion after laser treatment improved the shear bond strength.